Deciphering the molecular basis of mycobacteria and lipoglycan recognition by the C-type lectin Dectin-2 - Decout,A; Silva-Gomes,S; Drocourt,D; Blattes,E; Riviere,M; Prandi,J; Larrouy-Maumus,G; Caminade,A-M; Hamasur,B; Kallenius,G; Kaur,D; Dobos,KM; et al. (Scientific Reports, 2018)
Dectin-2 is a C-type lectin involved in the recognition of several pathogens such as Aspergillus fumigatus, Candida albicans, Schistosoma mansonii, and Mycobacterium tuberculosis that triggers Th17 immune responses. Identifying pathogen ligands and understanding the molecular basis of their recognition is one of the current challenges. Purified M. tuberculosis mannose-capped lipoarabinomannan (ManLAM) was shown to induce signaling via Dectin-2, an activity that requires the (α1 → 2)-linked mannosides forming the caps. Here, using isogenic M. tuberculosis mutant strains, we demonstrate that ManLAM is a bona fide and actually the sole ligand mediating bacilli recognition by Dectin-2, although M. tuberculosis produces a variety of cell envelope mannoconjugates, such as phosphatidyl-myo-inositol hexamannosides, lipomannan or manno(lipo)proteins, that bear (α1 → 2)-linked mannosides. In addition, we found that Dectin-2 can recognize lipoglycans from other bacterial species, such as Saccharotrix aerocolonigenes or the human opportunistic pathogen Tsukamurella paurometabola, suggesting that lipoglycans are prototypical Dectin-2 ligands. Finally, from a structure/function relationship perspective, we show, using lipoglycan variants and synthetic mannodendrimers, that dimannoside caps and multivalent interaction are required for ligand binding to and signaling via Dectin-2. Better understanding of the molecular basis of ligand recognition by Dectin-2 will pave the way for the rational design of potent adjuvants targeting this receptor.